HUBUNGAN ANTARA TIPE KEPRIBADIAN MENURUT EYSENCK DENGAN KOMITMEN ORGANISASI PADA OSIS SMAN 2 CIMAHI - Asep Abdul Kadir; Fenti Hikmawati; Witrin Gamayanti (Psympathic : Jurnal Ilmiah Psikologi, 2012)
This research based on phenomena of students council in which teamwork is really needed to get the organization goal. Before having teamwork, individu must have commitment to organization and level of commitment is assumed correlated with personality types. Eysenck (1974) defined personality as a result of interaction between inherited factors and surrounding. According to Porter (Schultz, 1982: 4), commitment on organization is individual attitude having trust and acceptance to the goal and values of organization. This research used correlational methodology. Result found  χ2hitung is 5.013 which is compared to χ2tabel 3.84 (Siegel, 1997: 301). Since χ2hitung = 5.013 is  more than χ2tabel 3.84 on significant level 0,05, then Ho is not accepted. Therefore, it is concluded that there is correlation between personality type and organizational commitment.